Selective increase of in vivo firing frequencies in DA SN neurons after proteasome inhibition in the ventral midbrain. (25th July 2014) - Subramaniam, Mahalakshmi; Kern, Beatrice; Vogel, Simone; Klose, Verena; Schneider, Gaby; Roeper, Jochen
Abstract The impairment of protein degradation via the ubiquitin‐proteasome system (UPS) is present in sporadic Parkinson's disease (PD), and might play a key role in selective degeneration of vulnerable dopamine (DA) neurons in the substantia nigra pars compacta (SN). Further evidence for a causal role of dysfunctional UPS in familial PD comes from mutations in parkin, which results in a loss of function of an E3‐ubiquitin‐ligase. In a mouse model, genetic inactivation of an essential component of the 26S proteasome lead to widespread neuronal degeneration including DA midbrain neurons and the formation of alpha‐synuclein‐positive inclusion bodies, another hallmark of PD. Studies using pharmacological UPS inhibition in vivo had more mixed results, varying from extensive degeneration to no loss of DA SN neurons. However, it is currently unknown whether UPS impairment will affect the neurophysiological functions of DA midbrain neurons. To answer this question, we infused a selective proteasome inhibitor into the ventral midbrain in vivo and recorded single DA midbrain neurons 2 weeks after the proteasome challenge. We found a selective increase in the mean in vivo firing frequencies of identified DA SN neurons in anesthetized mice, while those in the ventral tegmental area (VTA) were unaffected. Our results demonstrate that a single‐hit UPS inhibition is sufficient to induce a stable and selective hyperexcitability phenotype in surviving DA SN neurons in vivo. This might imply that UPS dysfunction sensitizes DA SN neurons by enhancing 'stressful pacemaking'.